MEMPELAJARI PENGARUH PENAMBAHAN TEPUNG BUNGA KECOMBRANG (Nicolaia spesiosa Horan) SEBAGAI PENGAWET ALAMI TERHADAP DAYA SIMPAN BAKSO IKAN GABUS - Yusuf, M.Handhi; Dasir, Dasir (Edible: Jurnal Penelitian Ilmu-ilmu Teknologi Pangan, 2014)
This research aims to study the effect of adding flour to the shelf life of flowers kecombrang cork fish balls. This study was conducted in laboratory of the Faculty of Agriculture, University of Muhammadiyah Palembang in April 2014 through the month of December 2014. This study used a randomized block design (RAK) are arranged in a non fakorial with 5 (five) factors that repeated treatment as much as 5 (five) times. The level of treatment factor adding interest kecombrang flour used in this study are: T0 (Addition kecombrang flour 0,00%), T1 (addition of flour kecombrang 1.00%), T2 (addition of flour kecombrang 2.00%), T3 (The addition of flour kecombrang 3.00%) and, T4 (addition of flour kecombrang4.00%). Based on the results of measurements of water content and protein content meatballs before and after 5 days of storage showed that the concentration of flour kecombrang interest as a natural preservative very significant effect on the moisture content and protein content meatballs before and after 5 days of storage. The highest water levels before 5 days of storage are in treatment T4 (adding flour kecombrang interest 4.00%) with an average value of 68.054% and the lowest on the T0 (adding flour kecombrang interest 0,00%) with an average value of 66 , 269%. The highest water levels after 5 days of storage are on the T0 (adding flour kecombrang interest 0,00%) with an average value of 73.219% and the lowest in treatment T4 (adding flour kecombrang interest 4.00%) with an average value of 72.539 %. The highest protein content before 5 days of storage are in treatment T4 (adding flour kecombrang interest 4.00%) with an average value of 12.32% and the lowest on the T0 (adding interest flour kecombrang 0.00%) with a mean value average 12.02%. The highest protein content after 5 days of storage are in treatment T4 (adding flour kecombrang interest 4.00%) with an average value of 11.62% and the lowest on the T0 (adding interest flour kecombrang 0.00%) with a mean value average 9.19%. Organoleptic taste, flavor, color and elasticity retributions cork fish balls before and after storage on average preferably at T4 treatment (adding flour kecombrang interest 4.00%).